Eccrine Hidrocystoma in a Child: An Atypical Presentation - Nam, Jae-Hui (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2010)
Eccrine hidrocystomas are small benign cystic lesions that normally affect only adult females. Eccrine hidrocystoma is characterized by tense vesicles that are predominately located on the face and particularly on the periorbital areas. Histologically, eccrine hidrocystoma consists of one or more partially collapsed unilocular cysts in the dermis, and these cysts are often situated adjacent to normal eccrine ducts. An 8-year-old boy presented with multiple skin-colored to bluish tiny papules on his nose. Histopathologically, the dilated partial cystic structures in the middermis were lined by one or two layers of flattened or cuboidal epithelial cells. We report here on an atypical presentation of multiple eccrine hidrocystomas that were localized on the nose of a child.